Evaluation of the need for education of a patient with ischemic heart disease - Maciej Zajdel; Bożena Baczewska; Beata Kropornicka; Cecylia Olszak; Bożena Muraczyńska; Alina Dzirba; Robert Jan Łuczyk (Kazimierz Wielki University, 2018)
SUMMARY Cardiovascular diseases are still a serious problem both in the world and in Polish society. It is estimated that in Poland they are responsible for almost half of deaths. The basis for counteracting this trend is first and foremost prevention of primary as well as secondary prevention. It seems that the main activity in this area is to conduct extensive educational activities aimed at both risk factors, prevention principles and the need to make changes in lifestyle.The study was conducted using the case-by-case study method, using the proprietary questionnaire for studying the level of knowledge about ischemic heart disease. In addition, for the purpose of a more complete assessment, techniques for observation, intelligence and document analysis were also used. Based on the analysis of the results, a number of knowledge deficits were found in the patient both in terms of basic risk factors as well as the principles of prophylaxis of ischemic heart disease. The study also shows that it is important to conduct education in the scope of the disease and the characteristic symptoms of myocardial ischemia, as well as the symptoms of myocardial infarction. Correct knowledge of these symptoms will allow for a faster diagnosis of life-threatening conditions and to take prompt and effective treatment. The obtained results of own research coincide with the research carried out by other Polish researchers.